Synthesis and Characterization of 1-(1-naphthyl)-5-phenyl-2,4-pentadien-1-one from trans-cinnamaldehyde and 1-acetonaphthone - Dori Fitria; Bayu Ardiansah; Atia Balkis (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Chalcone analogues (1-(1-naphthyl)-5-phenyl-2,4-pentadiene-1-one) have been synthesized through an aldol condensation reaction between cinnamaldehyde and 1-acetylnaphthalene. The method used in this study is the stirrer method, with the reaction conducted at room temperature for 24 hours using a NaOH catalyst in H2O/ethanol (50%, v/v). The purity of the product was analyzed using thin-layer chromatography on silica gel plates with n-hexane: ethyl acetate (9:1) employed as the solvent. The resulting product obtained was 0.88 g with a yield of 61.97%. Structure Analysis and elucidation of the synthesized compounds were performed by measuring the vibrations of the functional groups using FTIR, LCMSMS analysis, and determining the 1H and 13C atoms by HNMR and CNMR analysis. The FTIR, LCMSMS, 1H, and 13C NMR analysis identified that the synthesized product as chalcone analogues, specifically 1-(1-naphthyl)-5-phenyl-2,4-pentadiene-1-one.